Ultralow-viscosity brominated cardanol as well as preparation method and application thereof
By preparing ultra-low viscosity brominated cardisenol, the problem of high viscosity of existing flame retardants is solved, the flame retardant performance and flexibility of polyurethane foam is improved, the low viscosity requirements of spraying construction is met, and the biomass material is reduced Environmental pollution.
Patent Information
- Application Number
- CN202411208027.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-14
AI Technical Summary
The existing bromine flame retardants have high viscosity in polyurethane foam materials, which is difficult to meet the low viscosity requirements of spraying construction, and traditional flame retardants have problems with environmental pollution and resource consumption.
By reacting cashew phenol with bromine and acid anhydrides, ultra-low viscosity brominated cashew phenol is prepared, combining its bio-based and benzene ring structure, improving its flexibility and flame retardant properties, and meeting low viscosity and high performance need.
The low viscosity characteristics of bromine flame retardant are achieved, the flame retardant properties and high temperature resistance of polyurethane foam are improved, the fluidity requirements of on-site construction are met, and the use of biomass materials is used to reduce environmental pollution.
Smart Images

Figure CN119306605A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer flame retardant materials, and in particular to an ultra-low viscosity brominated cardanol, a preparation method thereof, and an application thereof. Background Art
[0002] At present, the world's economy still relies mainly on petrochemicals. However, due to the consumption of fossil resources and the pollution of the environment, there is an urgent need to find alternatives to fossil resources, among which biomass is the most promising candidate. As an agricultural by-product, cardanol is extracted from natural plant oils and has the advantages of abundant sources, low prices and renewable nature. At the same time, the unique C15 long-chain structure of cardanol gives it good flexibility and hydrophobicity; the benzene ring gives it excellent rigidity.
[0003] Polyurethane (PU) is a polymer with repeating carbamate groups (-NHCOO-) in the polymer backbone structure. Polyurethane foam has very excellent physical and chemical properties, such as low thermal conductivity, high strength, excellent adhesion and mechanical properties. It is an important polymer foam material and is widely used in construction, transportation, packaging, furniture and aviation industries. In 2022, the global polyurethane production reached 24 million tons, of which soft foam and hard foam accounted for 52% of the market. Polyurethane foam is a porous material and easy to burn. The limiting oxygen index value (LOI) of polyurethane foam material that has not been flame retardant modified is only 18%. If 20% of polyurethane foam is flame retardant, it is estimated that 250,000 tons of flame retardant will be required. In order to pursue high performance, the common brominated flame retardants on the market currently use raw materials with benzene ring structures. These raw materials themselves are liquids or powders with higher viscosity at room temperature. After bromination, they are mostly liquids or powders with higher viscosity, which cannot meet the low viscosity requirements of spray construction. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the above-mentioned technology, to provide an ultra-low viscosity brominated cardanol and a preparation method and application thereof, so as to achieve the requirement of low viscosity of the brominated flame retardant for spraying construction.
[0005] To this end, the present invention provides an ultra-low viscosity brominated cardanol having a structure shown in the following formula (1):
[0006]
[0007] Wherein, R is an alkyl group or a halogenated alkyl group; R1 is a carbon 15-alkyl side chain of cardanol; and x is any real number from 1 to 3.
[0008] Preferably, the ultra-low viscosity brominated cardanol has a viscosity of 2000 cPs or less at 25°C.
[0009] Preferably, the viscosity of the ultra-low viscosity brominated cardanol at 25° C. is less than 1000 cPs. The present invention also provides a method for preparing the ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0010] Step S1. dissolving cardanol in an organic solvent I, adding an acetic acid solution containing bromine, and after the reaction is complete, washing the organic phase with water, separating the liquids, and distilling off the organic solvent I under reduced pressure to obtain a brominated intermediate;
[0011] Step S2. The brominated intermediate obtained in step S1 is dissolved in an organic solvent II, and an acid anhydride substance is added to react under the action of a catalyst. After the reaction is complete, the organic phase is washed with water, separated, and the organic solvent II is distilled off under reduced pressure to obtain the ultra-low viscosity brominated cardanol.
[0012] Preferably, the organic solvent I or the organic solvent II is selected from carbon tetrachloride, chloroform, dichloromethane, dichloroethane and the like.
[0013] Preferably, the acid anhydride substance is selected from one or more of acetic anhydride, propionic anhydride, ethylpropionic anhydride and chloroacetic anhydride.
[0014] Preferably, the catalyst is selected from one or more of p-toluenesulfonic acid, acetyl chloride, thionyl chloride and concentrated sulfuric acid.
[0015] Preferably, in step S1, 270-340 parts of cardanol are weighed and dissolved in 300-500 parts of organic solvent I, and 285-590 parts of acetic acid solution containing bromine are added dropwise at the same time. After the addition is completed, the reaction is carried out. After the reaction is complete, the organic phase is sequentially washed with alkali, washed with water, separated, and the organic solvent I is distilled off under reduced pressure to obtain a brominated intermediate.
[0016] Preferably, in step S2, 500-750 parts of the brominated intermediate obtained in step S1 are weighed and dissolved in 600-900 parts of organic solvent II, 90-110 parts of acetic anhydride and 2-3 parts of p-toluenesulfonic acid are added to react, and after the reaction is complete, the organic phase is fully washed with water, separated and the organic solvent II is distilled off under reduced pressure to obtain the ultra-low viscosity brominated cardanol.
[0017] Preferably, in step S1, the reaction temperature is 40°C; in step S2, the reaction temperature is 30°C.
[0018] The use of the low-viscosity multifunctional phosphate flame retardant described above or the ultra-low viscosity brominated cardanol prepared by any of the ultra-low viscosity brominated cardanol preparation methods described above, wherein the ultra-low viscosity brominated cardanol is used as a polymer flame retardant in a flame-retardant polyurethane foaming composition.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The main raw material of the present invention is cardanol, which has the advantages of being cheap, abundant in source, non-toxic and biodegradable.
[0021] 2) The synthesized ultra-low viscosity brominated cardanol connects cardanol and gives it the benzene ring and long-chain structure of cardanol, bringing flexibility, low toxicity, water resistance and high temperature resistance.
[0022] 3) The synthesized bio-based amino polyol brominated epoxy resin contains bromine (Br) flame retardant groups, which can effectively improve the flame retardant properties of foam materials.
[0023] 4) The synthesized ultra-low viscosity brominated cardanol can meet the low viscosity requirements of brominated flame retardants in on-site construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application.
[0025] Figure 1 is the infrared spectrum of cardanol;
[0026] Figure 2 This is the infrared spectrum of the ultra-low viscosity brominated cardanol prepared in Example 1 and Example 2. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0028] Unless otherwise specified, the methods used in the present invention are all conventional methods; the raw materials and devices used are all conventional commercially available products unless otherwise specified.
[0029] Cardanol was purchased from Zhejiang Wansheng Co., Ltd.;
[0030] Isocyanate (PM200), polyether polyol (4110), silicone oil (ZL-5), triethylenediamine (A33), and dibutyltin dilaurate (T12) were purchased from Changzhou Zhuolian Zhichuang Polymer Material Technology Co., Ltd.;
[0031] Acetic anhydride was purchased from Shandong Jiachi New Chemical Co., Ltd.;
[0032] Bromine was purchased from Shandong Tianyi Chemical Co., Ltd.;
[0033] Tetrabromophthalic anhydride diol was purchased from Shandong Runke Chemical Co., Ltd.;
[0034] Antimony trioxide was purchased from Hunan Jinbo New Material Technology Co., Ltd.;
[0035] The viscometer model is NDJ-8S, 1# rotor, purchased from Shanghai Lichen Bangxi Instrument Technology Co., Ltd.
[0036] The present invention prepares ultra-low viscosity brominated cardanol, and the chemical structure is shown in the following formula (1):
[0037]
[0038] Wherein, R is an alkyl group or a halogenated alkyl group; R1 is a carbon 15-alkyl side chain of cardanol; and x is any real number from 1 to 3.
[0039] Example 1
[0040] This embodiment provides a method for preparing ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0041] (1) Weigh 270 g of cardanol and dissolve it in 300 g of carbon tetrachloride. At the same time, add acetic acid solution containing 285 g of bromine dropwise. After the addition is completed, the temperature is raised to 40° C. and the mixture is kept warm for 5 hours. After the reaction, the mixture is washed once with a sodium bicarbonate solution and then washed three times with water. The mixture is separated and the carbon tetrachloride solvent is distilled off under reduced pressure to obtain a brominated intermediate.
[0042] (2) Weigh 500 g of the above brominated intermediate and dissolve it in 600 g of carbon tetrachloride, add 90 g of acetic anhydride and 2 g of p-toluenesulfonic acid, react at 30° C. for 2 h, wash with water three times after the reaction, separate the liquids, and distill off the carbon tetrachloride solvent under reduced pressure at 50° C.-80° C. to obtain ultra-low viscosity brominated cardanol.
[0043] Example 2
[0044] This embodiment provides a method for preparing ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0045] (1) Weigh 340 g of cardanol and dissolve it in 500 g of carbon tetrachloride. At the same time, add acetic acid solution containing 590 g of bromine dropwise. After the addition is completed, the temperature is raised to 40° C. and the mixture is kept warm for 5 hours. After the reaction, the mixture is washed once with a sodium bicarbonate solution and then washed three times with water. The mixture is separated and the carbon tetrachloride solvent is distilled off under reduced pressure to obtain a brominated intermediate.
[0046] (2) Weigh 750 g of the above brominated intermediate and dissolve it in 900 g of carbon tetrachloride, add 110 g of acetic anhydride and 3 g of p-toluenesulfonic acid, react at 30° C. for 2 h, wash with water three times after the reaction, separate the liquids, and distill off the carbon tetrachloride solvent under reduced pressure at 50° C.-80° C. to obtain ultra-low viscosity brominated cardanol.
[0047] Example 3
[0048] This embodiment provides a method for preparing ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0049] (1) Weigh 300 g of cardanol and dissolve it in 400 g of carbon tetrachloride. At the same time, add 420 g of bromine in acetic acid solution drop by drop. After the addition is completed, heat it to 40°C and keep it warm for 5 hours. After the reaction, wash it once with sodium bicarbonate solution and then wash it three times with water. Separate the liquids and distill off the carbon tetrachloride solvent under reduced pressure to obtain a brominated intermediate.
[0050] (2) Weigh 620 g of the above brominated intermediate and dissolve it in 700 g of carbon tetrachloride, add 102 g of acetic anhydride and 2.5 g of p-toluenesulfonic acid, react at 30° C. for 2 h, wash with water three times after the reaction, separate the liquids, and distill off the carbon tetrachloride solvent under reduced pressure at 50° C.-80° C. to obtain ultra-low viscosity brominated cardanol.
[0051] In order to confirm the successful synthesis of ultra-low viscosity brominated cardanol, infrared analysis was performed on cardanol, Example 1 and Example 2. First, infrared detection was performed on cardanol, and the results are shown in the attached figure. Figure 1 Shown: 3338.2cm -1 The broad absorption peak corresponding to the phenolic hydroxyl group -OH, 3011.1 cm -1 Cardanol C 15 The stretching vibration absorption peak of the long-chain carbon-carbon double bond is 2924.3 cm -1 and 2853.5cm -1 Corresponding to the stretching vibration absorption peak of CH on methyl and methylene, 1587.5cm -1 、1486.8cm -1 and 1455.6cm -1 is the stretching vibration absorption peak of the benzene ring in cardanol. The infrared spectra of Example 1 and Example 2 are shown in the attached Figure 2 As shown in the figure: compared with cardanol, new absorption peaks appeared. Among them, 1770.5cm -1 is the stretching vibration absorption peak of C=O, 1192.3cm -1 is the stretching vibration absorption peak of COC, 737.5cm -1 is the stretching vibration absorption peak of C-Br. In addition, Example 1 and Example 2 have a peak at 3338.2 cm -1 The broad absorption peak of phenolic hydroxyl group -OH disappears; Example 1 at 3011.1cm -1The absorption peak at 3011.1cm is smaller, and the absorption peak of Example 2 at this point is almost gone. It can be seen from the above infrared that compared with cardanol, the product after the reaction has obvious C=O and COC stretching vibration absorption peaks and the broad absorption peak of cardanol phenolic hydroxyl -OH disappear, indicating that cardanol has been completely esterified. The stretching vibration absorption peak of C-Br indicates that Br has been successfully introduced. In addition, Example 1 at 3011.1cm -1 The absorption peak at 47° becomes smaller, and the absorption peak of Example 2 at this point almost disappears, indicating that the introduction of Br not only occurs in the substitution reaction on the benzene ring, but also in the addition reaction of the double bond in the side chain of cardanol. At the same time, according to the following bromine content test results, it is shown that cardanol has been successfully brominated and esterified to generate the corresponding products.
[0052] The viscosity and bromine content of the ultra-low viscosity brominated cardanol prepared in Example 1, Example 2 and Example 3 were measured respectively, and the results are shown in Table 1 below. As shown in Table 1, the ultra-low viscosity brominated cardanol prepared in Example 1, Example 2 and Example 3 have viscosities of 780 cPs, 1900 cPs and 1270 cPs at 25°C, respectively, all of which have low viscosity characteristics of no more than 2000 cPs, among which Example 1 has an ultra-low viscosity of no more than 1000 cPs. In addition, the bromine content results show that the bromine content of Example 1 is 43.1%; the bromine content of Example 2 is 54.3%; and the bromine content of Example 3 is 48.1%, and the results are consistent with theoretical calculations. The above infrared spectrum and bromine content test results show that Example 1, Example 2 and Example 3 have successfully prepared ultra-low viscosity brominated cardanol.
[0053] Table 1 Determination results of viscosity and bromine content of target products of Examples 1 to 3
[0054] Viscosity (25℃, cPs) Bromine content (%) Example 1 780 43.1 Example 2 1900 54.3 Example 3 1270 48.1
[0055] Comparative Example 1
[0056] This comparative example provides a method for preparing ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0057] (1) 300 g of cardanol, 100 g of acetic anhydride and 1.5 g of p-toluenesulfonic acid were weighed into a four-necked flask, reacted at 30° C. for 2 h, washed with water three times after the reaction, separated, and the carbon tetrachloride solvent was distilled off under reduced pressure at 50° C.-80° C. to obtain an intermediate.
[0058] (2) Weigh 350 g of the intermediate and dissolve it in 500 g of carbon tetrachloride. At the same time, add dropwise an acetic acid solution containing 320 g of bromine. After the addition is completed, the temperature is raised to 40° C. and the mixture is kept warm for 5 hours. After the reaction, the mixture is washed once with a sodium bicarbonate solution and then washed three times with water. The mixture is separated and the carbon tetrachloride solvent is distilled off under reduced pressure to obtain ultra-low viscosity brominated cardanol.
[0059] Comparative Example 2
[0060] This comparative example provides a method for preparing ultra-low viscosity brominated cardanol, comprising the following preparation steps:
[0061] (1) The content of this step is the same as that of step (1) of Comparative Example 1 and will not be described again.
[0062] (2) This step differs from step (2) of comparative example 1 in that an acetic acid solution containing 530 g of bromine is added dropwise. The other contents are the same and will not be described again here; ultra-low viscosity brominated cardanol is obtained.
[0063] Compared with Example 1 and Example 2, the post-bromination method was adopted in the synthesis process of Comparative Example 1 and Comparative Example 2. In the preparation of ultra-low viscosity brominated cardanol of Comparative Example 1 and Comparative Example 2, it was found that during the water washing process of step (2), the aqueous solution had varying degrees of residual bromine; among them, this phenomenon was more serious in Comparative Example 2.
[0064] The viscosity and bromine content of the ultra-low viscosity brominated cardanol prepared in Comparative Example 1 and Comparative Example 2 were measured respectively, and the results are shown in Table 2 below.
[0065] Table 2 Results of determination of viscosity and bromine content of target products of Comparative Example 1 and Comparative Example 2
[0066]
[0067]
[0068] As can be seen from Table 2, the bromine contents of the ultra-low viscosity brominated cardanol prepared in Comparative Example 1 and Comparative Example 2 are 38.9% and 43.1%, respectively. Compared with Example 1 and Example 2, when the same mass of bromine acetic acid solution is added, the bromine content of the product is significantly reduced. According to preliminary analysis, on the one hand, after the esterification reaction between the phenolic hydroxyl group in cardanol and acetic anhydride, the steric hindrance is significantly increased, which affects the subsequent bromination reaction; on the other hand, compared with the -OR after esterification, the -OH of cardanol has a stronger electronegativity, which can increase the electron cloud density on the benzene ring to a greater extent, making the activity of the benzene ring higher and more conducive to the reaction.
[0069] Polyurethane foam test
[0070] Preparation of foaming material: Turn on the balance and preheat it for more than 5 minutes, calibrate it if necessary, and place a film plastic bag in the wooden box.
[0071] First, according to Table 3 "Formula of Polyurethane Foam Flame Retardant System", introduce polyether polyol into disposable plastic cup, put other reagents (except isocyanate) into the plastic cup, stir and mix at a speed of about 1000r / min, and use it as white material. Isocyanate itself is used as black material. Set the temperature of the thermostat to the required temperature (T = 25℃), constant material temperature T1 = T2 = T (if it is a water bath thermostat, pay attention to the protection of the raw materials from water absorption) Put the disposable cup on the balance and reset it; pour in the amount of white material designed in the formula and reset it. Add the amount of black material designed in the formula according to the ratio coefficient. First, stir the black and white material mixture slowly (turn on the stopwatch at the same time) to avoid splashing and affecting the ratio; stir at full speed for 8-10 seconds after 2-3 seconds (try to shorten the operation time of the above two steps). Then quickly pour the stirred raw materials into a plastic cup or wooden box and let it foam freely. After the foaming stops, place it in a natural environment and continue to react for 24 hours.
[0072] According to the LOI foam material test standard, the sample size (length, width and thickness) should be 70-150mm×10±0.5mm×10±0.5mm; (Test standard: GB / T2406-93 standard, determination of limiting oxygen index of foam plastics).
[0073] According to the UL94 foam material test standard, the sample strip size (length, width and thickness) should be 150mm×50mm×thickness 3-13mm (10mm is used in this application), (test standard: UL94 foam material test standard).
[0074] LOI test method: clamp a sample of a certain size vertically in a transparent combustion tube with a sample clamp, in which there is an upward flow of oxygen and nitrogen mixed in a certain proportion. Light the upper end of the sample, observe the subsequent combustion phenomenon, and record the continuous combustion time or the distance burned. When the burning time of the sample exceeds 3 minutes or the flame front exceeds the 50mm mark, reduce the oxygen concentration. When the burning time of the sample is less than 3 minutes or the flame front does not reach the mark, increase the oxygen concentration. Repeat this operation, gradually approaching the specified value from the upper and lower sides until the concentration difference between the two is less than 0.5%.
[0075] Table 3 Polyurethane foam flame retardant system formula
[0076]
[0077] Table 3 studies the flame retardant properties of polyurethane materials prepared by different formulations. On the basis of the typical formulation, the polyurethane foam synthesized by adding tetrabromophthalic anhydride diol (bromine content of 44%), a flame retardant with excellent flame retardant properties on the market, has an LOI value of 23.1%, and UL-94 is V-0 level; in comparison, the LOI value of the polyurethane foam added with the same mass of the flame retardant of Example 1 (bromine content of 43.1%) is 23.3%; the LOI value of the polyurethane foam added with the same mass of the flame retardant of Example 2 (bromine content of 54.3%) can reach 24.3%, and the UL-94 of both can reach V-0 level, showing excellent flame retardant properties.
[0078] In summary, the present invention provides a method for preparing ultra-low viscosity brominated cardanol and its application. The ultra-low viscosity brominated cardanol is synthesized by first brominating cardanol and then using anhydride esterification. The synthesized ultra-low viscosity brominated cardanol contains the flame retardant group bromine (Br), which can be applied to the fields of flame retardant epoxy resins, coatings, and polyurethane foams. In addition, the viscosity of the ultra-low viscosity brominated cardanol of the present invention can reach less than 1000cPs. In particular, for the construction of irregular spaces such as exterior wall insulation and pipelines at the polyurethane foaming site, the present invention can maintain good fluidity after mixing black material and white material, and can quickly fill the required area during the construction process, which can solve the problems of difficult spraying construction, insufficient filling, and poor compatibility caused by the fact that most brominated flame retardants in the current polyurethane field are powders or liquids with higher viscosity.
[0079] It should be noted that the present invention provides a method for preparing ultra-low viscosity brominated cardanol, wherein:
[0080] (1) The organic solvent used in step (1) and step (2) may be carbon tetrachloride, or may be one of chloroform, dichloromethane, dichloroethane, and the like.
[0081] (2) The acid anhydride substance used in step (2) may be acetic anhydride, or one or more of propionic anhydride, ethylpropionic anhydride, chloroacetic anhydride, etc.
[0082] (3) In addition to p-toluenesulfonic acid, the catalyst used in step (2) may also be one or more of acetyl chloride, thionyl chloride, concentrated sulfuric acid, and the like.
[0083] (4) The reaction temperatures of step (1) and step (2) can be set according to actual conditions. In Examples 1 and 2, the reaction temperature of step S1 is 40° C. and the reaction temperature of step S2 is 30° C., which are both preferred reaction temperatures.
[0084] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. An ultra-low viscosity brominated cardanol, characterized in that: It has the structure shown in the following formula (1): Wherein, R is an alkyl group or a halogenated alkyl group; R1 is a bromine-containing cardanol carbon 15-decyl side chain; and x is any real number from 1 to 3.
2. The ultra-low viscosity brominated cardanol according to claim 1, characterized in that: Its viscosity at 25°C is less than 2000 cPs.
3. A method for preparing ultra-low viscosity brominated cardanol as claimed in claim 1, characterized in that: The method comprises the following preparation steps: Step S1. dissolving cardanol in an organic solvent I, adding a solution containing bromine, and after the reaction is complete, washing the organic phase with water, separating and removing water, and distilling off the organic solvent I under reduced pressure to obtain a brominated intermediate; Step S2. The brominated intermediate obtained in step S1 is dissolved in an organic solvent II, and an acid anhydride substance is added to react under the action of a catalyst. After the reaction is complete, the organic phase is washed with water, separated and dehydrated, and the organic solvent II is distilled off under reduced pressure to obtain the ultra-low viscosity brominated cardanol.
4. The method for preparing ultra-low viscosity brominated cardanol according to claim 3, wherein the organic solvent I or the organic solvent II is selected from one of carbon tetrachloride, chloroform, dichloromethane and dichloroethane.
5. The method for preparing ultra-low viscosity brominated cardanol according to claim 3, characterized in that: The acid anhydride substance is selected from one or more of acetic anhydride, propionic anhydride, ethylpropionic anhydride and chloroacetic anhydride.
6. The method for preparing ultra-low viscosity brominated cardanol according to claim 3, characterized in that: The catalyst is selected from one or more of p-toluenesulfonic acid, acetyl chloride, thionyl chloride and concentrated sulfuric acid.
7. The method for preparing ultra-low viscosity brominated cardanol according to claim 3, characterized in that: In the step S1, 270-340 parts of cardanol are weighed and dissolved in 300-500 parts of organic solvent I, and acetic acid solution containing 285-590 parts of bromine is added dropwise at the same time. After the addition is completed, the reaction is carried out. After the reaction is complete, the organic phase is sequentially washed with alkali, washed with water, separated, and the organic solvent I is distilled off under reduced pressure to obtain a brominated intermediate.
8. The method for preparing ultra-low viscosity brominated cardanol according to any one of claims 3 to 7, characterized in that: In the step S2, 500-750 parts of the brominated intermediate obtained in the step S1 are weighed and dissolved in 600-900 parts of organic solvent II, and 90-110 parts of acetic anhydride and 2-3 parts of p-toluenesulfonic acid are added to react. After the reaction is complete, the organic phase is fully washed with water, separated and the organic solvent II is distilled off under reduced pressure to obtain the ultra-low viscosity brominated cardanol.
9. The method for preparing ultra-low viscosity brominated cardanol according to claim 8, characterized in that: In the step S1, the reaction temperature is 40°C; in the step S2, the reaction temperature is 30°C.
10. Use of the low-viscosity multifunctional phosphate flame retardant according to claim 1 or 2 or the ultra-low viscosity brominated cardanol prepared by the method for preparing ultra-low viscosity brominated cardanol according to any one of claims 3 to 8, characterized in that: The ultra-low viscosity brominated cardanol is used as a polymer flame retardant in a flame retardant polyurethane foaming composition.
Citation Information
Cited By
Phosphorus-bromine synergistic cardanol polyol as well as preparation method and application thereof
CN122145509A
A cashew phenol polyol with phosphorus-bromine synergism and a preparation method and application thereof
CN122145509B